Trajno ohranjanje računalniških programov - Vodopivec, Tadej (Knjižnica, 2011)
Comtrade Ltd. covers a wide range of activities related to information and communication technologies; its deliverables include web applications, locally installed programs, system software, drivers, embedded software (used e.g. in medical devices, auto parts, communication switchboards). Also the extensive knowledge and practical experience about digital long-term preservation technologies have been acquired. This wide spectrum of activities puts us in the position to discuss the often overlooked aspect of the digital preservation - preservation of software programs. There are many resources dedicated to digital preservation of digital data, documents and multimedia records, but not so many about how to preserve the functionalities and features of computer programs. Exactly these functionalities - dynamic response to inputs - render the computer programs rich compared to documents or linear multimedia. The article opens the questions on the beginning of the way to the permanent digital preservation. The purpose is to find a way in the right direction, where all relevant aspects will be covered in proper balance. The following questions are asked: why at all to preserve computer programs permanently, who should do this and for whom, when we should think about permanent program preservation, what should be persevered (such as source code, screenshots, documentation, and social context of the program - e.g. media response to it ...), where and how? To illustrate the theoretic concepts given the idea of virtual national museum of electronic banking is also presented.
Keywords: računalniški programi; digitalni viri; arhiviranje; trajno ohranjanje